2000
DOI: 10.1590/1809-43922000301105
|View full text |Cite
|
Sign up to set email alerts
|

On the occurrence of cyanolipids In Paullinia carpopodea cambess And P. cupana Kunth seed oils

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 6 publications
(6 reference statements)
2
9
0
Order By: Relevance
“…Previous investigations (19)(20)(21)(22) on the total FA composition of the seed oils from members of the Sapindaceae family showed that they are very peculiar in that cis-vaccenic and paullinic acids are major constituents and of chemotaxonomic importance. Our previous analysis of the seed oil of P. cupana (6) also confirmed those findings.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations (19)(20)(21)(22) on the total FA composition of the seed oils from members of the Sapindaceae family showed that they are very peculiar in that cis-vaccenic and paullinic acids are major constituents and of chemotaxonomic importance. Our previous analysis of the seed oil of P. cupana (6) also confirmed those findings.…”
Section: Resultsmentioning
confidence: 99%
“…Seeds from this plant contain high amounts of caffeine and are also used to prepare a very popular carbonated soft drink in Brazil. Within the genus Paullinia, the species P. elegans (10), P. meliaefolia (5)(6)(7), P. tomentosa, and P. carpopodea (11,12) have been studied previously for the lipid content of their seed oils. Investigations on the oil composition of P. cupana have been limited and controversial (11,12).…”
mentioning
confidence: 99%
“…Within the genus Paullinia, the species P. elegans (10), P. meliaefolia (5)(6)(7), P. tomentosa, and P. carpopodea (11,12) have been studied previously for the lipid content of their seed oils. Investigations on the oil composition of P. cupana have been limited and controversial (11,12). It was reported, for example, that the presence of CL and the cyanogenic features of the plant may depend on the different origins of the seeds (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Eicosanoic acid (20:0) and eicosenoic acid (20:1 n-9) are present in high proportion in many species (Aichholz et al 1997). In the genus Paullinia, the rare fatty acids paullinic acid (Z-13-eicosenoic acid) and cis-vaccenic acid (Z-11-octadecenoic acid) are ubiquitous constituents (Seigler 1974;Spitzer 1995;Spitzer 1996;Lago et al 2000;Avato et al 2003). Other fatty acids found go from dodecanoic (12:0) to docosanoic acids (22:0) (Mikolajczak et al 1970a;1970b;1971;Aichholz et al 1997;Avato et al 2003).…”
Section: Cyanocompoundsmentioning
confidence: 99%